ETHIC CYBER STRENGTHENING ASCRIMINAL LAW POLICY FORMULATIONS IN RESPONSE CYBERPORN - Hervina Puspitosari; Ashinta Sekar Bidari (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Cyber Porn is an act of using cyberspace to create, display, distribute, publish pornography and obscene material. Cyberspace with technology that carries pornography, so that pornography provides more feature-rich form of pornography, pornografipun experienced media translation and making pornography created with multi features. The lack of regulations on the provision of criminal sanctions for internet access service providers (ISP /Internet Service Provider)are not filtering out pornographic content so that they can be accessed internet users. Cyber ethics required for casting activity that is passed by internet users. Ideal criminal Legal policy of studies necessary legal substance of law reforms in the fight against cyberporn.